Relation Between Event-Related Potential Latency and Saccade Latency in Overt Shifts of Attention. (April 2020) - Kulke, Louisa; Atkinson, Janette; Braddick, Oliver
Controlled shifts of attention between competing stimuli are crucial for effective everyday visual behaviour. While these typically involve overt shifts of fixation, many past studies used covert attention shifts in which fixation is unchanged, meaning that some response components may result from the inhibition of eye movements. In this study, the neural events in the human brain when making overt shifts of attention are studied through the combination of event-related potential recording with simultaneous eye tracking. Fixation shifts under competition (central target remains visible when a peripheral target appears) were compared with noncompetition (central target disappears). A longer latency for competition compared with noncompetition, which is found in the saccadic response, is already present in the early occipital positivity when a single target is presented for the fixation shift. These results indicate that the requirement to disengage from a current target affects the time course of neural processing at an early level. However, the relation is more complex when the participant is required to choose which of two targets to fixate.